Flannery O'Connor - American Writers 54 : University of Minnesota Pamphlets on American Writers - Hyman, Stanley Edgar, 1919-1970 (Book collections on Project MUSE., 1966)
Flannery O'Connor - American Writers 54 was first published in 1966. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.